SAT0288 CHARACTERIZATION OF ANTI-AMINOACYL TRNA SYNTHETASE AUTOANTIBODIES IN PATIENTS WITH IDIOPATHIC INFLAMMATORY MYOPATHIES. (2nd June 2020) - Preger, C.; Notarnicola, A.; Hellström, C.; Wigren, E.; Cerqueira, C.; Nilsson, P.; Lundberg, I. E.; Persson, H.; Gräslund, S.; Jakobsson, P. J.
Abstract : Background: Idiopathic inflammatory myopathies (IIM) are rare chronic inflammatory diseases associated with high mortality and morbidity [1]. One sub-group of IIM, anti-synthetase syndrome (ASS), is characterized by the presence of autoantibodies that target aminoacyl transfer(t) RNA synthetases (aaRS), together with specific clinical manifestations such as myositis, interstitial lung disease (ILD), arthritis, mechanic's hand, Raynaud's syndrome and fever [2]. The most common anti-aaRS autoantibody, anti-Jo1 targeting histidyl tRNA synthetase (HisRS), is present in up to 20-30% of patients with IIM, and up to 90% of patients with myositis and ILD [3, 4]. Besides Jo1, there are today seven other identified autoantigens within the aaRS family. Objectives: A large part of patients with IIM, including individuals with clinical manifestations indicating ASS, test seronegative to all known myositis specific autoantibodies. However, these patients could potentially harbor autoantibodies against targets not tested for in clinic. In this study, we aimed at extending the detection of autoantibodies by including all cytoplasmic aaRS in the analysis of patients with IIM. We hypothesized the existence of new potential autoantigens within this protein family. Methods: The presence of anti-aaRS autoantibodies was determined using a multiplex suspension bead array assay on 242 IIM patients from the Karolinska University Hospital myositis cohort. A panel of 186 recombinant constructs, representing 57 proteins that included full-length or partial sequence overlaps between constructs of all cytoplasmic aaRS as well as other myositis related proteins, were coupled to magnetic color-coded beads and each plasma sample was tested against the complete antigen panel. Results: By the use of this multiplex method we identified patients with autoantibodies against many of the tested aaRS. Autoantibodies binding to HisRS have previously been shown to bind with higher reactivity to the WHEP domain of HisRS and this was also confirmed in this study. We confirmed reactivity against three of the other aaRS tested for in the clinic (PL-12, PL-7, and EJ). In addition, we identified patients positive for anti-Zo, -KS and -HA, autoantibodies usually not screened for in routine. Finally, our data indicates that there are autoantibodies binding to other aaRS than the previously known eight autoantigens, which will be presented. Conclusion: In this study, we could detect autoantibodies in plasma from patients with IIM, both against the most common aaRS autoantigens, but also against other aaRS that are usually not tested for in clinic. We conclude that it is important to continue the studies of anti-aaRS autoantibodies, and their correlation to clinical manifestations, and in the long run also include more aaRS autoantigens in clinical practice. References: [1]Dobloug, G.C., et al., Mortality in idiopathic inflammatory myopathy: results from a Swedish nationwide population-based cohort study. Ann Rheum Dis, 2018. 77(1): p. 40-47. [2]Barsotti, S. and I.E. Lundberg, Myositis an evolving spectrum of disease. Immunol Med, 2018. 41(2): p. 46-54. [3]Vencovsky, J., H. Alexanderson, and I.E. Lundberg, Idiopathic Inflammatory Myopathies. Rheum Dis Clin North Am, 2019. 45(4): p. 569-581. [4]Richards, T.J., et al., Characterization and peripheral blood biomarker assessment of anti-Jo-1 antibody-positive interstitial lung disease. Arthritis Rheum, 2009. 60(7): p. 2183-92. Disclosure of Interests: Charlotta Preger: None declared, Antonella Notarnicola: None declared, Cecilia Hellström: None declared, Edvard Wigren: None declared, Catia Cerqueira: None declared, Peter Nilsson: None declared, Ingrid E. Lundberg Grant/research support from: Bristol Meyer Squibb, Corbus Pharmaceuticals, Inc and Astra Zeneca, Helena Persson: None declared, Susanne Gräslund: None declared, Per-Johan Jakobsson Shareholder of: Gesynta Pharma, Grant/research support from: Gesynta Pharma, AstraZeneca,